Response to Christopher P. Muzzillo's Comments on "Introduction of a Novel Figure of Merit for the Assessment of Transparent Conductive Electrodes in Photovoltaics: Exact and Approximate Form". Issue 23 (3rd May 2022) - Anand, Aman; Islam, Md Moidul; Meitzner, Rico; Schubert, Ulrich S.; Hoppe, Harald
Abstract: Similarities and differences between figure of merits (FOMs) for the assessment of transparent conductive electrodes (TCEs) are discussed. This article is a response to C. P. Muzzillo's comment on the introduction of the novel FOM (the so‐called exact FOM or Anand's FOM) and it deals with questions about how implicit and how exact the different approaches really are and whether specific application cases can be covered or not. While the exact FOM has been introduced to provide an upper limit of photovoltaic power conversion efficiency for the whole range of possible transmittance and sheet resistance values of transparent conductive oxides, Muzzillo's comment points out specific application cases, that have to be treated with more individual modeling. In this work, the authors adopt these application cases into the exact FOM to demonstrate its applicability. Furthermore, the FOM approximation given by Muzzillo is used and slightly refined, yielding an even better agreement with the exact FOM. In the end, it is concluded that both approaches are justified: Muzzillo's FOM for very practical applications and Anand's (exact) FOM for fundamental assessment. In this work, both approaches have been harmonized to yield an ultimate tool for the future development of TCEs for photovoltaics. Abstract : This response discusses the implicitness and preciseness of the figures of merit (FOM) ϕMuzzillo and ϕAnand (respectively, ϕexact, the exact FOM) for the quantitative assessment of transparent conductive electrodes (TCEs). It is shown that the ϕAnand remains exact for various application cases when serial interconnection and the addition of a metal grid within the one diode model are considered.